Rechtliche Beurteilung von Mikrotransaktionen und Lootboxen - Busch, Max (Universitätsverlag Göttingen, 2022)
The purchase of additional items in videogames, also called 'Microtransactions', has recently grown to become one of the dominating methods of monetization in the games industry. However, many versions of these monetization schemes face severe backlash because it appears that the ways to monetize games are increasingly influencing the contents of the medium and that those games are purposefully designed to bring vulnerable players to spend more money than they meant to. In this thesis, those points of criticism were taken into consideration and as a starting point to explore the legality of these kinds of monetization schemes from a legal standpoint. This was done with regards to the Unfair Competition Law, Youth Protection regulation and general civil law. Also, the chance-based variant of microtransactions, the so called 'Lootboxes', have been examined with regard to their legality under gambling regulations.